Literary Traditions: English in Malaysia and Singapore (Column 7) - Quayum, Mohammad Abdul (The Daily Star, Bangladesh, 2014)
There are quite a few anthologies and individual collections of short stories that have come out since the publication of Lloyd Fernando's Twenty-Two Malaysian Short Stories (1968) and MalaysianShort Stories (1981). Some of the early short stories were also published in local journals and magazines, such as LIDRA and Tengarra. Many of these stories focus on poverty and destitution in Malaysian society in order to expose its class and caste hierarchy. They also argue that indigence is not a race problem but a class problem; the oppressed and the humiliated are found in all the various ethnic groups in the country. Poverty was acute in Malaysian society in the aftermath of independence because of the Japanese Occupation and the Communist insurgency in the forties and the fifties respectively, which had thrown the country's export economy into disarray, causing, as historians Andaya and Andaya suggest, widespread “unemployment, food shortages, poverty, poor health and general uncertainty.” But poverty still remains a problem in some sectors of the society, in spite of the country's phenomenal economic growth in the last twenty years. This is because of the lack of equitable distribution of wealth among its citizens.